ISSUES ENCOUNTERED IN SPORTS ACTIVITIES AND OPPORTUNITIES FOR TECHNOLOGY USE - Barno Pulatovna Abdullaeva (Web of Journals Publishing, 2024)
This article discusses the possible issues while doing sport activities with technologies and finding solutions to deal with those accrued problems. Additionally in this article here are shown body parts and its diagrams to give some understandings to the learners. Also, students being taught to make a goal in is his career and life as well
Keywords: ability, children and adolescents, tactical thinking, body parts, physical fitness, goal.